The Scale of Fluctuations of the Zloty’s Exchange Rate Against Selected Currencies in the Years of 2009–2014 – an Analysis of Empirical Data - Michalczyk, Wawrzyniec (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
After a period of significant variations, since 2012 the zloty’s exchange rate has undergone visible stabilization. Although the level of Polish currency’s relation to the euro is the most significant for Polish economy, it is also vital to analyze its value against the dollar or other currencies, issued by the most important economic partners. The aim of the article is to characterize the volatility of the zloty and identify key trends in this field. The author presents the results of analysis of the relation of Polish currency to the euro and to the dollar, and further also to other major currencies, i. e. Swiss franc, British pound, Czech koruna, Russian ruble and Chinese yuan. As a research method, the indicator analysis of statistical data, including correlation analysis, was used. The research period covers 1.08.2009–31.07.2014. The analysis of fluctuations in the zloty’s exchange rate confirmed an observation about increased stability of Polish currency’s relation since 2012, which is especially important with regard to the exchange rate against the euro, because while in the ERM2, the reduction of its volatility is crucial for the selection of the economic policy’s variant conducted by the authorities. Basing on the research, it was also possible to state generally that the relation of the zloty against the euro is more stable than against the dollar and that the value of the PLN seems to be more closely linked to the EUR than to the USD.